The Role of Film as an Alternative Media in the Learning Process - Zulfiah Larisu; Syailendra Reza Irwansyah Rezeki; Lidia Djuhardi (HK-Publishing, 2022)
AbstractThe research intended to see a film become an alternative media in the learning process. Film that are commonly considered as entertainment media, turns out it has the potential to be a source of learning because there are some messages or values that are useful in the development of human coginitive. Research data obtained from documents like thesis as primary data. Data analysis uses discourse analysis method to find out the influence of film as an alternative media in the learning process. The ideas in this article are described descriptively, based on the studies that have been done, seeing the relationship between the film and the learning process.Keywords: Film, Education, Sociology of Education AbstrakPenelitian ini bertujuan untuk melihat film menjadi media alternatif dalam proses pembelajaran. Film yang biasa dianggap sebagai media hiburan, ternyata berpotensi menjadi sumber belajar karena terdapat beberapa pesan atau nilai yang bermanfaat dalam perkembangan kognitif manusia. Data penelitian diperoleh dari dokumen-dokumen seperti skripsi sebagai data primer. Analisis data menggunakan metode analisis wacana untuk mengetahui pengaruh film sebagai media alternatif dalam proses pembelajaran. Ide-ide dalam artikel ini dijelaskan secara deskriptif, berdasarkan studi yang telah dilakukan, melihat hubungan antara film dan proses pembelajaran.Kata kunci: Film, Pendidikan, Sosiologi Pendidikan